Visualization of vascular mural cells in developing brain using genetically labeled transgenic reporter mice. Issue 3 (March 2018) - Jung, Bongnam; Arnold, Thomas D; Raschperger, Elisabeth; Gaengel, Konstantin; Betsholtz, Christer
The establishment of a fully functional blood vascular system requires elaborate angiogenic and vascular maturation events in order to fulfill organ-specific anatomical and physiological needs. Although vascular mural cells, i.e. pericytes and vascular smooth muscle cells, are known to play fundamental roles during these processes, their characteristics during vascular development remain incompletely understood. In this report, we utilized transgenic reporter mice in which mural cells are genetically labeled to examine developing vascular mural cells in the central nervous system (CNS). We found platelet-derived growth factor receptor β gene ( Pdgfrb )-driven EGFP reporter expression as a suitable marker for vascular mural cells at the earliest stages of mouse brain vascularization. Furthermore, the combination of Pdgfrb and NG2 gene (Cspg4) driven reporter expression increased the specificity of brain vascular mural cell labeling at later stages. The expression of other known pericyte markers revealed time-, region- and marker-specific patterns, suggesting heterogeneity in mural cell maturation. We conclude that transgenic reporter mice provide an important tool to explore the development of CNS pericytes in health and disease.